(untitled) (Research, Society and Development, 2023)
Beer is very popular in Brazil, and the country is the third largest consumer of this drink, after China and United States. At the international level, there are records of fatal episodes attributed to the ingestion of fermented beverages (beers and wines) containing ethylene glycol and diethylene glycol since the 1980s. In Brazil, a recent case (2020), which led to fatal victims, was associated with ingestion of beer contaminated with ethylene glycol. In this work, a mini literature review was carried out in order to characterize the current understanding regarding the origin and risks associated with the presence of glycols in beverages. The survey led to the conclusion that acute and lethal effects can only come from relatively high doses from exogenous contamination (accidental or criminal). However, Saccharomyces cerevisiae yeasts have the potential to secrete ethylene glycol through the metabolic degradation of xylose, a five-carbon sugar that comes from hemicellulose. Spontaneous formation levels are usually low, with no risk of acute/fatal toxicity, but the potential for chronic toxicity due to a cumulative effect must be considered. Periodic monitoring of ethylene glycol and diethylene glycol levels in beers is proposed, in view of the relevance of this beverage among Brazilian consumption habits.